„Nie zapomnij mnie”. O filmowo-ekonomicznej przestrzeni w dziejowości Wrocławia 1896–1945 - Gierszewska, Barbara Lena (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2020)
The author of the reviewed book for the first time shows how and why film preferences of the inhabitants of Breslau in the years 1896–1932 and 1933–1945 differed in relation to the choices of cinema audiences in other European cities during the same period. He uses the POPSTAT statistical method proposed for this purpose by the German researcher Joseph Potter. He also uses the scientific ideas of „attraction cinema” developed by André Gaudreault. He bases his research on analyzing film success rankings and to measure viewer preferences.